Rice Husk‐Based 3D Porous Silicon/Carbon Nanocomposites as Anode for Lithium‐Ion Batteries. Issue 6 (2nd May 2019) - Fan, Xiaoyong; Yin, Baipeng; Wu, Tianhui; Feng, Man; Zhang, Guang Cong; Li, Siheng; Tang, Shoufeng; Gu, Jianmin; Wen, Bin; Lu, Li
Abstract : Silicon/carbon (Si/C) nanocomposites with 3D porous structure are prepared by a high‐temperature hydrothermal treatment and subsequent magnesiothermic reduction using rice husks (RHs) and NaCl as Si/C sources and potential porogens. In this strategy, interconnected and uniform nanopores are introduced into RHs under the assistance of NaCl and high pressure while the organic components are carbonized, and the intermediate products (porous SiO2 /C nanocomposites) are formed. The porous structure is maintained well during the high‐temperature hydrothermal treatment. After the magnesiothermic reduction of the porous SiO2 /C nanocomposites, a 3D porous Si/C nanocomposite is formed, which provides rapid transferring channels for the lithium ions and accommodates volumetric changes during electrochemical cycling, leading to an improved electrochemical performance. Abstract : A 3D porous rice husk (RH)‐based silicon/carbon (Si/C) nanocomposite is produced by the magnesiothermic reduction of the 3D porous RHs‐SiO2 /C nanocomposite formed via high‐temperature hydrothermal treatment of RHs in NaCl aqueous solution, and delivers 345 mAh g −1 after 100 cycles at 50 mA g −1 .